(untitled) (Research, Society and Development, 2020)
Objective: The objective of this study was to describe the importance of nursing care for patients with maxillofacial trauma. Methods: The integrative research method was used, in which 10 scientific articles made available in full, in the last 10 years, selected from the Virtual Health Library (VHL) and Scientific Electronic Library Online (SciELO), comprised the analyzed sample. Results: The results showed that in all publications, nursing was essential in all phases that involved the initial care in urgency and emergency, aiming at the stabilization of the patient, going through surgery, rehabilitation and, his reinsertion in society, prioritizing a agile, quality, safe, individualized and comprehensive service. It was also analyzed that even in face of such importance there is a limited number of publications not only involving nursing, but other professionals who are fundamental in the recovery of these patients. Conclusion: It is concluded that this study will contribute to enhance, even more, nursing care for trauma victims and in particular face trauma, stimulating interest for new research related to the theme and also involving other essential professional areas. in the recovery and social reintegration process of these patients.